E(x)=(2x+1/x+1)+[2(x+2)/(x+1)•(x+2)-x+1/(x+2)•(x+1)]•x*2-4/x*2+x-6=
Aratati ca E(x)=2
Răspunsuri la întrebare
Răspuns de
0
2x + 1 2x + 4 x +1 ( x -2 ) · ( x +2 )
E = ------------ +[ ------------------- - --------------------- ] · -------------------------- =
x +1 ( x +1) ·(x +2) ( x +1) ·( x +2 ) ( x +3) · ( x -2 )
2x +1 x + 3 x +2
= ---------------- + ------------------------- · -------------- =
x +1 (x +1 ) ·( x +2 ) x +3
2x +1 1 2x + 2 2 · ( x +1 )
= ------------ + ---------------- = ------------- = ------------------------ = 2
x + 1 x +1 x +1 x +1
E = ------------ +[ ------------------- - --------------------- ] · -------------------------- =
x +1 ( x +1) ·(x +2) ( x +1) ·( x +2 ) ( x +3) · ( x -2 )
2x +1 x + 3 x +2
= ---------------- + ------------------------- · -------------- =
x +1 (x +1 ) ·( x +2 ) x +3
2x +1 1 2x + 2 2 · ( x +1 )
= ------------ + ---------------- = ------------- = ------------------------ = 2
x + 1 x +1 x +1 x +1
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă